2019
DOI: 10.1111/jpm.12545
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effectiveness of staffing levels on conflict and containment on psychiatric wards in England

Abstract: Accessible Summary What is known on the subject? Literature on staffing levels and outcomes in psychiatric wards is limited and shows mixed associations Lack of economic evidence on conflicts and containment in psychiatric care Data from the City‐128 study showed that regular qualified nurse staffing levels in the preceding shifts were associated with raised conflict and containment levels What this paper adds to existing knowledge? This is the first economic analysis using the City‐128 data, with costs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
4
1
Order By: Relevance
“…For the verbal aggression and property damage incidents similar results were found as for physical aggression. These findings are not in line with the literature reporting an association of high bed occupation with aggression and coercive measures, but add to research pointing at a link between staffing and incidents ( 56 ). The authors acknowledge that there may be “complex organizational and relational factors that need further research to fully understand the overall context” (p. 1).…”
Section: Resultscontrasting
confidence: 99%
“…For the verbal aggression and property damage incidents similar results were found as for physical aggression. These findings are not in line with the literature reporting an association of high bed occupation with aggression and coercive measures, but add to research pointing at a link between staffing and incidents ( 56 ). The authors acknowledge that there may be “complex organizational and relational factors that need further research to fully understand the overall context” (p. 1).…”
Section: Resultscontrasting
confidence: 99%
“…Of the 56 studies located in the search process, 16 were related to three datasets from programs of research by Bowers and colleagues investigating conflict and containment rates and various nursing and other variables in acute psychiatric inpatient wards (Baker et al, 2009; Bowers, 2009; Bowers, Allan, et al, 2007; Bowers, Allan, Simpson, Jones, Van Der Merwe, & Jeffery, 2009; Bowers, Allan, Simpson, Jones, & Whittington, 2009; Bowers & Crowder, 2012; Bowers et al, 2006, 2012, 2013; Bowers, Flood, et al, 2008; Bowers, Jeffery, et al, 2007; Bowers, Whittington, et al, 2008; Bowers et al, 2010; E‐Morris et al, 2010; Kartha & McCrone, 2019; Papadopoulos et al, 2012; Stewart & Bowers, 2012). Conflict and containment are patient behaviours and staff actions that form a significant part of the nurse–patient relationship in acute psychiatric inpatient wards (Bowers, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Kartha and McCrone (2019) also used the dataset to conduct an economic evaluation using three different staffing levels. The cost‐effectiveness analysis of the three staffing scenarios showed that the low staff scenario was cost‐effective in terms of conflicts and containment averted.…”
Section: Resultsmentioning
confidence: 99%
“…Use of these technologies is justified on the basis that they may be able to detect or prevent aggressive and violent incidents, reduce self-harm incidents and suicide attempts, improve staff and patient safety, change patient behaviour and staff conduct, provide accurate records to help resolve complaints and to contribute to legal cases, and reduce staffing costs [13,14,15,16,17]. Reducing cost is a driving force for many service providers, and both conflict on wards and providing adequate staffing are costly [18] but interrelated [19,20]; surveillance technologies may therefore appear to offer a cost-effective solution.…”
Section: Introductionmentioning
confidence: 99%